Public Transport Integration - Poliak, Milos; Mrnikova, Michaela; Jaskiewicz, Marek; Jurecki, Rafal; Kaciakova, Barbora (Communications - Scientific letters of the University of Zilina, 2017)
The importance of the issue of an effective mode of passenger transport is currently increasing. On the one hand there is an increasing economic demand for public passenger transport, on the other hand, there is a growing traffic share of individual automobile transport. The aim of this article is to define the importance of public passenger transport and to identify the problems of its operation. The integration of different modes of public passenger transport is proposed as a way to increase the competitiveness of public passenger transport. This paper analyses the individual elements of integration systems abroad and suggests the methodology of integration system applicable in regions where the share of public passenger transport is decreasing within the transport market.